The Cognitive Control of Eating and Body Weight: It’s More Than What You “Think” - Davidson, Terry L.; Jones, Sabrina; Roy, Megan; Stevenson, Richard J. (Frontiers in Psychology, 2019)
Over the past decade, a great deal of research has established the importance of cognitive processes in the control of energy intake and body weight. The present paper begins by identifying several of these cognitive processes. We then summarize evidence from human and nonhuman animal models, which shows how excess intake of obesity-promoting Western diet (WD) may have deleterious effects on these cognitive control processes. Findings that these effects may be manifested as early-life deficits in cognitive functioning and may also be associated with the emergence of serious late-life cognitive impairment are described. Consistent with these possibilities, we review evidence, obtained primarily from rodent models, that consuming a WD is associated with the emergence of pathophysiologies in the hippocampus, an important brain substrate for learning, memory, and cognition. The implications of this research for mechanism are discussed within the context of a “vicious-cycle model,” which describes how eating a WD could impair hippocampal function, producing cognitive deficits that promote increased WD intake and body weight gain, which could contribute to further hippocampal dysfunction, cognitive decline, and excess eating and weight gain.